Tra Montaccianico e Firenze : gli Ubaldini e la città : atti del convegno di studi, Firenze-Scarperia, 28-29 Settembre, 2012 - Monti, Alessandro,; Pruno, Elisa, (Limina/limites ;, 2016)
The central theme The Ubaldini and the City is the classic confrontation between feudal society and a resurgent urban form as the central instrument of organisation of European society, which is crucial to the origins of Europe as we know it today. The analysis starts from a reconstruction of the historical role played by the Ubaldini on the basis of a critical reconsideration of the available documentary evidence, and the results appear to be perfectly consistent with the general pattern for the Florentine aristocracy. The theme is one of 'boundaries': between historical and archaeological evidence, between the late Middle Ages and the birth of modernity; it concerns space with the establishment of new 'borders' which evolve from Terra Nuova and become completely territorial.